Cognitive Overload, Emotional Exhaustion, and Psychological Disengagement among Political Science Lecturers in Nigerian Universities - Kate Ekedama; Daniel Mevayerore Igbini (CV. Gerasi Insan Nusantara, 2026)
Psychological disengagement among university lecturers, encompassing absenteeism and reduced mental engagement, poses a serious threat to teaching quality and institutional effectiveness. This study examined cognitive overload and emotional exhaustion as predictors of psychological disengagement among Political Science lecturers in Nigerian universities, while considering differences across university ownership. A quantitative correlational survey design was employed, involving a population of 4,500 lecturers, with 400 selected through multistage sampling. Data were collected using adapted versions of the NASA Task Load Index, the Maslach Burnout Inventory–Educators Survey, and work withdrawal behaviour measures. Validity was confirmed through expert review and exploratory factor analysis, and reliability was established with Cronbach’s alpha values ranging from 0.84 to 0.89.Analysis using descriptive statistics, one-way ANOVA, and simple linear regression at the 0.05 significance level revealed that psychological disengagement did not differ across university ownership. Cognitive overload was not a significant predictor, indicating that high mental demands alone do not drive disengagement. In contrast, emotional exhaustion significantly predicted psychological disengagement and accounted for a substantial portion of its variance, with lecturers experiencing higher emotional exhaustion more likely to withdraw from their duties. These findings highlight emotional exhaustion as the principal psychological driver of disengagement among Political Science lecturers. Universities are encouraged to implement structured counseling services, stress management programs, peer support systems, and balanced workload allocation. Additionally, initiatives promoting recovery and well-being, such as regular breaks and flexible scheduling, can sustain lecturers’ engagement, reduce psychological disengagement, and enhance instructional quality. Prioritizing staff well-being is therefore essential for improving academic delivery and overall institutional effectiveness in Nigerian universities.